ЎҚУВЧИЛАРДА АХБОРОТ ТАҲДИДИНИНГ ОЛДИНИ ОЛИШ УСУЛЛАРИ - Ёзиева, У. (SCIENCE and SOCIETY, 2016)
In the article we deal with a special program, worked out in informational threatening and methods of extracurricular lessons on prevention and formation of immunity in the students of general educational secondary schools.